2000
DOI: 10.3130/aija.65.39_3
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Non-Specific Evaluation of the Combined Environment of Color and Temperature

Abstract: Effects ofwaml color and cool color o ガ lthem 】 al sensation ' 「 , the , 「 impression ofhet − cold ' 「 and the I' impression ofwarm ・ cool 「 , were discussed experimentally under the thermal conditions of20 and 24 ℃ in winter and 24 and 29℃ in summer , Significant effect ofboth colors ori themmal sensation was shown under the 29 ℃ in summer . The effect of colors on the ' 「 impression ofhot − coldl ' and the I' impression ofwarm − cool ' , was 1arger than that on thermal sensation . It was assumed that the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Nagano et al (1996) showed that environmental factors not thought to be directly relevant influence each environmental factor, and that specific evaluations of environmental factors on several scales influences evaluations specific to other environmental factors. Matsubara et al (2000) evaluated color conditions closer to everyday life, showing that the reducing effects of psychological load on heat through visual factors are greater with regard to cool colors on the high temperature side and warm colors on the low temperature side. In addition, a linear regression of the relationship between thermal sensation and temperature showed that adding visual and auditory factors decreased the gradient of the regression formula (i.e., the response to thermal environmental factors in relation to the increase in room temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Nagano et al (1996) showed that environmental factors not thought to be directly relevant influence each environmental factor, and that specific evaluations of environmental factors on several scales influences evaluations specific to other environmental factors. Matsubara et al (2000) evaluated color conditions closer to everyday life, showing that the reducing effects of psychological load on heat through visual factors are greater with regard to cool colors on the high temperature side and warm colors on the low temperature side. In addition, a linear regression of the relationship between thermal sensation and temperature showed that adding visual and auditory factors decreased the gradient of the regression formula (i.e., the response to thermal environmental factors in relation to the increase in room temperature).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the research shows a clear inclination toward lower values once the ETF peak of 28-29°C is exceeded. Research by Matsubara et al [5], focusing primarily on psychological assessment, shows that, in slightly uncomfortable, warmer environmental conditions, an ameliorative effect on high thermal sensation was shown in the cool/ warm category as opposed to in the thermal sensation category in indoor settings. In addition, in research by Shimada et al [22], also focusing primarily on psychological assessment in indoor settings, the gradient of the regression coefficient was smaller for non-singular cool/warm impressions as opposed to singular thermal sensation impressions of heat.…”
Section: Etf and Cool/warm Sensationmentioning
confidence: 99%
“…In qualitative visual stimuli testing conducted by Matsubara et al [5], amelioration of the psychological influence (perceived high temperatures) was significant in relation to both hot and cold environments deemed slightly uncomfortable. The level of improvement engendered by fuller vegetation with regard to thermal environments was greater than that yielded by flatter vegetation cover [7].…”
Section: Visual Stimuli and Influence On The Human Bodymentioning
confidence: 99%
See 2 more Smart Citations